Cognitive style and educational performance. The case of public schools in Bogotá, Colombia - Hederich-Martínez, Christian; Camargo-Uribe, Angela (Educational psychology (Dorchester-on-Thames), 2016)
This study analyses the relationships among educational performance, field dependence-independence cognitive style and factors traditionally associated with performance and style, to build a comprehensive model of factors associated with the levels of education performance of students in Bogotá. A total of 3003 students, of grades 8 and 10, from 62 public schools of the city of Bogotá, Colombia participated in the study. An analysis of multiple correspondences and a path analysis were carried out. A relationship between cognitive style and educational performance was found: field-independent students are more likely to obtain high-performance levels both in standardised tests and in teachers' evaluations. The path analysis shows that there are two directions in the association: a direct path leads to a positive association: higher levels of field independence produce better performances; an indirect path leads to a negative association: higher levels of field independence produce indiscipline and, consequently, lower performances.